Incidence of solid organ cancers after liver transplantation: comparison with regional cancer incidence rates and risk factors. (21st January 2015) - Carenco, Christophe; Faure, Stéphanie; Herrero, Astrid; Assenat, Eric; Duny, Yohan; Danan, Guillaume; Bismuth, Michaël; Chanques, Gérald; Ursic‐Bedoya, José; Jaber, Samir; Larrey, Dominique; Navarro, Francis; et al.
Abstract Background & Aims Increased rates of solid organ cancers post‐liver transplantation have been reported, but the contribution of environmental factors and immunosuppressive therapy is not clear. This study's aims were to compare the incidence of de novo solid organ cancers after liver transplantation; identify risk factors independent of immunosuppressive therapy associated with these cancers; and assess the influence of calcineurin inhibitors on the appearance of these cancers. Methods This single‐centre study from 1991 to 2008 included 465 liver recipients who had survived for ≥1 year. Gross incidence rates were standardized by age and sex, using the global population as a reference. In addition, 322 of the 465 patients treated for ≥1 year with calcineurin inhibitors were studied. Results Sixty‐five (13.9%) of the 465 patients developed de novo solid cancers. The overall relative risk was 3.7. Significantly increased relative risks were observed for digestive, oesophageal, colorectal, oral and lung cancers, but not for genito‐urinary and breast cancers. Among the 65 patients who developed solid organ cancers, 43 died (66.1%), 41 from cancer. The two independent risk factors were pretransplant smoking [P < 0.0001; odds ratio = 5.5 (.5; 12)] and obesity [P = 0.0184; odds ratio = 2.2 (1.1; 4.3)]. Of the 322 patients on calcineurin inhibitors, 55 (17%) developed de novo solid cancers. Tacrolimus exposure level was a risk factor for de novo solid cancers [P < 0.0001; OR = 15.3 (4.5; 52.2)]. Conclusions We recommend a change in immunosuppressive protocols with lifestyle/dietary guidelines and smoking cessation.